The role of aesthetics in learning science in an art-science lesson. Issue 5 (24th March 2022) - Hannigan, Shelley; Wickman, Per-Olof; Ferguson, Joseph Paul; Prain, Vaughan; Tytler, Russell
ABSTRACT : In this paper, we analyse results from one classroom session within an 8-week program in which Year 10 students constructed 'trash' puppets of endangered Australian animals. In making the puppets and using them as part of a 'theatre in a suitcase' performance at Melbourne Zoo, students were expected to integrate both scientific and artistic goals to demonstrate knowledge of specific endangered species. In this process, students needed to learn how their more immediate, everyday positive and negative aesthetic responses could be made continuous with a scientific aesthetic to produce both a coherent puppet and an advocacy performance. Through micro-ethnographic practical epistemology analysis of video data of this session, we demonstrate how this mix of everyday and subject-specific aesthetic responses, judgements and intentions interacted to shape and promote students' learning in science. In addressing this multimodal and multi-purpose task, students learnt and applied science knowledge to a real-world issue of species endangerment.